2017
DOI: 10.1007/s11186-017-9297-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of valuation: repertoires of worth at the financial margins

Abstract: This article draws upon thirteen months of ethnographic research in a Chicago pawnshop to show how prices of objects in pawnshops are actively, socially negotiated using what I term discursive strategies of valuation. Three kinds of discursive strategies of valuation emerge repeatedly in the data: a. references to the specific material attributes of the objects, b. references to the unique biographical histories of the objects, c. reference to the financial need and (relative) social positioning of the custome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At a micro level, asymmetries of power could be challenged interactionally. For instance, Degenshein (2017) observed in her ethnography of a Chicago pawnshop that in many cases where shopkeepers and clients negotiated the value of pawned objects, emphasizing need and lower socioeconomic status by the client actually increased the perceived value of a pawned object and resulted in a higher payment to the client. This example showcases, as Bandelj (2012) has proposed, that relational work may offer a chance to overcome the rigidity of status inequalities, even if temporarily.…”
Section: Consequences Of Relational Workmentioning
confidence: 99%
“…At a micro level, asymmetries of power could be challenged interactionally. For instance, Degenshein (2017) observed in her ethnography of a Chicago pawnshop that in many cases where shopkeepers and clients negotiated the value of pawned objects, emphasizing need and lower socioeconomic status by the client actually increased the perceived value of a pawned object and resulted in a higher payment to the client. This example showcases, as Bandelj (2012) has proposed, that relational work may offer a chance to overcome the rigidity of status inequalities, even if temporarily.…”
Section: Consequences Of Relational Workmentioning
confidence: 99%
“…The productive aspects of rhetoric have become clearer, however, in recent studies showing the centrality of language, discourses and narratives in structuring social change. Rhetorical factors have been emphasized in the emergence of economic models [Carruthers and Espeland 1991; McCloskey 1998], strategies of valuation [Degenshein 2017], and organizational change [Suddaby and Greenwood 2005]. This article demonstrates that rhetoric is also an important driver of institutional change in regulation.…”
Section: Rhetorical Metricsmentioning
confidence: 93%
“…Sociologists have observed that material objects can accrue moral and economic worth affecting how actors make decisions about the value of their health, possessions, finances, and the natural environment (Barnard 2016;Degenshein 2017;Fourcade 2011;Livne 2014;Zelizer 2010). "Humanitarian technologies" define, standardize, and commensurate what counts as sexual violence (Morse 2014), and end-of-life palliative care moralizes scarcity of material medical interventions (Livne 2014).…”
Section: Opioids and The Biomedicalization Of Sufferingmentioning
confidence: 99%